A review on the penal code: imposing harsher punishment against child rapist / Mohd Afif Ahmad Zamanhuri, Norsyazwani Abdullah and Nur Zalika Mohd Asri Redha. - Ahmad Zamanhuri, Mohd Afif; Abdullah, Norsyazwani; Mohd Asri Redha, Nur Zalika (2009)
This is a research project paper entitled "A Review on the Penal Code: Imposing Harsher Punishment towards Child Rapist". As the title suggest, our research will be conducted focusing mainly on the provision on the present punishment provided under the Penal Code. Besides analyzing the present punishment, a review on the local cases pertaining to statutory rape will also be observed. In addition, literature review will also be conducted as well as making reference to the other countries with regards to the issue of child rape. Besides adopting library based research, interviews will also be conducted to gain information from the related context, namely the psychological, social and legal aspect. As a result of the research, it is found that the present punishment entailed in the Penal Code is sufficient based on the certain basis. From the findings of our research, we have reached a conclusion that there is no need to impose harsher punishments. Accordingly, we have drawn out several recommendations based from what we have gain from this research beneficial to the public.